Vezels. - Armes, David (2021)
This print was created while artist-in-residence at Industriemuseum in Gent, Belgium for a week in late 2020. It is the fifth iteration of the Typographic Landscape series, considering how experience of place can be represented using the materials of typography and letterpress printing. 'Vezels' is the Dutch word for 'fibres' and the notion of this material, its origins and the way they are woven together seemed like a suitable mirror for the process of building up a printed piece.
Printed as artist-in-residence at Industriemuseum, Gent, Winter 2021
Erfgoedcollectie